Varicella seroprevalence in healthcare workers in a tertiary hospital: an audit of cross-sectional data. (December 2015) - Gorny, Alexander; Mittal, Chikul; Saw, Sharon; Venkatachalam, Indumathi; Fisher, Dale; Tambyah, Paul
Abstract Background The seroprevalence of varicella in Southeast Asia is not well described especially in healthcare workers (HCW) in the region. We report the varicella seroprevalence among healthcare workers from a diverse range of countries working in a tertiary care hospital in Singapore. Methods We audited the results of annual HCW health screening, which included a varicella assay, from the years 2009 to 2014. During this period, there was a change in hospital policy mandating varicella immunity for all newly employed healthcare workers. The serological data were reviewed with employment records on occupation and nationality. Seroprevalence rates were determined by standard commercial enzyme linked immunosorbent assays for each year of testing. Odds of being immune in 2014 were compared by means of multiple logistic regression. Results A total of 10, 585 samples were obtained from 6668 unique individuals over four separate cross-sections of the hospital workforce. A peak seroprevalence of 92.8 % (95 % CI 92.0–93.5) was recorded in 2014. Younger employees had a lower seroprevalence than their older colleagues. In a consolidated sample of 4875 members of the active workforce in October 2014, we identified that Indian nationals were less likely to be immune than their Singaporean national colleagues, odds ratio (OR) 0.26 (95 % CI 0.17–0.43, p < 0.001), while Chinese nationals were more likely to be immune, OR 4.34 (95 % CI 1.61–12.2, p = 0.004), after controlling for year of screening, gender, age-group and vocation. In 2014, being employed as administrative staff, OR 0.43 (95 % CI 0.29–0.64, p < 0.001) or contract service provider, OR 0.30 (95 % CI 0.19–0.47, p < 0.001), was also associated with a lower odds of being immune than being employed as a nurse. Conclusions There remain a small number of healthcare workers who are non-immune to varicella in our tertiary hospital. A new pre-employment policy of mandatory screening and vaccination may have increased rates of immunity but more needs to be done to ensure that all of our employees are immune to varicella to protect our vulnerable patients.